Comparative study on isolation techniques and characterization of Helicobacter pullorum in broiler chickens (Gallus sp.) and their farm environment in Selangor, Malaysia - Wai, Soe Soe (2012)
Helicobacter pullorum is becoming important as an emerging zoonotic pathogen. It has been isolated from poultry in many countries but reports are lacking in developing countries, including Malaysia. Helicobacter pullorum is a fastidious organism, and not readily culturable. They are generally misdiagnosed as Campylobacter and currently are identified by molecular method. This study was conducted to determine the appropriate isolation method, the prevalence of H. pullorum in broiler chickens and farm environment, antibiotic resistance and plasmid profiles of H. pullorum isolated and to characterize the H. pullorum isolates. The first part of the study showed 14 of 57 (24.6%) chickens from five farms were positive for H. pullorum of which 8 (14%) were co-colonized with Campylobacter species. In this study, three methods reported by other researchers were used (Method I, II & III) that is, based on Ceelen et al. (2006c) as method I, Zanoni et al. (2007) as method II and Miller et al. (2006) as method III. In two methods (method I & II), discrete colonies of H. pullorum were not obtained but were mixed with Campylobacter species, while (one) method III gave both discrete colonies of H. pullorum and mixed colonies. In terms of better isolation, ease of preparation and recovery of pure isolates, this (Method III) third method was the method of choice. To improve the H. pullorum isolation percentage, a further modification was done to this Method III by adding an enrichment step and modifying the incubation temperature. Using this modified method (Method IV), 24 of 30 (80.0%) chickens from three farms were positive for H. pullorum while only 17 of 30 (56.7%) were positive using Method III. Method IV gave a better recovery of H. pullorum from chicken caecal contents. The overall prevalence in the second part of the study showed H. pullorum was present in 51 % broilers using method IV alone in chickens from another ten farms, eight open-house farms and two close-house farms. From a total of 18 farms, 89 out of 187 (47.6%) chickens in which H. pullorum were isolated. Among them, 15 (8.0%) were co-colonized with Campylobacter spp. From environmental samples, all water samples were negative for H. pullorum while flies (17.5 %) and floor swab (30 %) samples were positive for H. pullorum and Campylobacter species, which are the risk factors for H. pullorum in chickens. The H. pullorum isolates were subjected to antibiotic susceptibility test using diffusion technique and M.I.C Evaluator method (M.I.C.E). All isolates were sensitive to polymyxin B but resistant to cephalothin. The pattern of resistance of the H. pullorum isolates to ciprofloxacin was 65.5% and 66.7%, and erythromycin 54.5% and 38.9%, cefotaxime 50.9% and 55.5%, ampicillin 25.5% and 38.9%, tetracycline 21.8% and 16.7%, and to gentamicin 10.9% and 5.6% by disc diffusion method and M.I.C.E, respectively. The overall difference in frequency of resistance was not significant between the two methods. The isolates showed 19 different antibiograms and were resistant to were ciprofloxacin and cefotaxime. Plasmids were detected in 12 out of 53 (22.6 %) antibiotic resistant isolates. Each isolate harboured two plasmids and the size ranged from 2.2 to 54 kb. The presence of plasmids in H. pullorum isolates did not correlate with the antibiotic resistance pattern. This study also showed that H. pullorum isolates were multi-resistant to four or more antibiotics at 18.2% and 11.1% as observed by disc diffusion method and M.I.C. Evaluator strips, respectively. From pulse field gel electrophoresis (PFGE), all 25 field isolates from eight different farms had distinct genotypes and most strains showed a high degree of genetic diversity. All isolates from different farms showed different fragment patterns; some were closely related while some were heterogeneous in the same farms. Thus, H. pullorum colonization in a farm may occur with a single strain that disseminated in the same flocks; clonal relationship may derived from the same sources and heterogeneous in isolates may be distributed from a common source of clonal origin. The PFGE analysis using SacII analysis was more discriminatory than using SmaI. To the author’s knowledge, this is the first study on H. pullorum in chickens in Malaysia. It is concluded from this study that H. pullorum is prevalent in chickens in the farms. The organisms may contaminate the carcasses during processing and at retailing and may be transmitted to humans through consumption of undercooked chicken meat or cause cross contamination of ready-to-eat food. The detection of multiantibiotic resistant isolates poses a threat to humans and further limits therapeutic options. Thus, with the increase in production of chicken meat, the contamination of such meat with foodborne pathogens including with H. pullorum is of considerable concern with regards to public health. Hence, it is recommended that farmers and processing operators be made aware of this and other foodborne pathogens that may be found in chickens. Therefore, the farmers need to adhere to good animal husbandry practices (GAHP) and meat processing operators to good manufacturing procedures (GMP).